Peranan Supervisi Dalam Pendidikan Islam - Herwadi (Proceedings of Annual Conference on Islamic Educational Management, 2021)
The educational supervision or as it is often known as education supervision has a basic concept that is closely related to education. In the basic concept of educational supervision explained a few basics about the concept of supervision in general. While the process of implementing supervision itself is a series that is carried out when supervision is carried out and the effort made by the supervisor in seeing and fostering the entire process of implementing education. In its development, the supervision of education has a good influence on the development of education, especially in Indonesia, especially Islamic education so that the level of professionalism of teachers in teaching can be realized optimally, both in madrasah and religious education teachers in public schools. Therefore, supervision is needed in the education process based on two important things. First, curriculum development is an indicator of educational progress. These developments often lead to changes in curriculum structure and function. Therefore the implementation of the curriculum requires continuous adjustments with real circumstances in the field. Second, the development of personnel, employees, or employees is always a continuous effort in an organization.